Evidence on the use of creatine in men or women practicing physical activity - Araujo, Sérgio de Sousa (2022)
The demand for physical activity in recent decades has increased both in the search for physical performance and for a better quality of life, and the market for supplements associated with both health and sports performance has also developed, one of the most nutritional supplements studied and creatine that, according to studies from 2018, 84% of the interviewees practiced physical activity, bodybuilding being the most performed and 22% continuous use of creatine, in the study in 2018, 93 subjects were interviewed, of which 91.4% were men where of these, 45% consumed creatine for its action to enhance physical and sports performance by giving more energy. Objective: to investigate the effects of creatine supplement in men and women who perform physical exercise. Methods: this is an integrative review, carried out in the BVS, SCIELO and PUBMED databases, using the descriptors nutritional supplements, creatine, training e wome as well as in English and Spanish in the periods from 2012 to 2022. Results: They identified in the studies carried out that when creatine is used combined with resistance training, they cause effects of potentiating some variables related to the human body, such as lean mass gain, increased muscle strength, increased muscle resistance and decreased muscle damage. Final considerations: It can be concluded that performing physical exerci.